Gas Chromatography Method Implementation to Determine Organophosphate Pesticide Residues in Kefamenanu Agricultural Land: Penerapan Metode Gas Chromatography Untuk Menentukan Residu Pestisida Organofosfat Pada Tanah Lahan Pertanian Kefamenanu - Marselina Theresia Djue Tea; Elisabeth Korbafo; Pudensia Ririn; Sanci Welmince Bani (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Pesticides are widely used in agriculture to prevent or control pests and diseases that interfere with or damage agricultural crops. However, excessive and inappropriate use of pesticides on agricultural land in Kefamenanu causes pesticide residues to remain on agricultural products and the environment. In this applied study, organophosphate pesticide residues were determined in agricultural soil with the aim of determining their presence and levels in the soil. The gas chromatography method was used. The analysis results obtained showed the detection of pesticide residues of chlorpyrifos, profenofos, and malathion. The retention time of each pesticide residue was 4.56 minutes, 3.68 minutes, and 3.35 minutes, which were in accordance with the retention time of each standard. The levels of pesticides chlorpyrifos, profenofos, and malathion were 1,817 mg/kg, 0.764 mg/kg, and 0.009 mg/kg, respectively. The results of the study showed that the levels of pesticide residues of chlorpyrifos and profenofos in the soil exceeded the maximum residue limit (MRL) that had been set. The malathion residue levels did not exceed the maximum residue limit. Thus, several recommendations are given that need to be implemented immediately.